Metabolic risk in patients participating in residential rehabilitation programs: how are we doing?. (April 2019) - Meehan, Tom; Jones, Donna; Stedman, Terry
Objectives: To examine the prevalence of metabolic syndrome and its association with clinical, demographic and lifestyle factors in patients with mental illness participating in residential rehabilitation. Methods: A physical health audit of all consumers ( n = 364) in publicly funded residential rehabilitation programs in Queensland was carried out in late 2016. Data collection focused on clinical, demographic and lifestyle factors associated with physical health. Results: Central obesity was identified in 80% of males and 89% of females and half of the patients (49.4%) met criteria for metabolic syndrome (MetS). The prevalence of MetS in Indigenous patients (66.1%) was 20% higher than the rate found in non-Indigenous patients (46.1%). Smoking, substance abuse, gender, Indigenous background, length of stay and rarely eating fruit and vegetables were individually associated with MetS. Conclusions: The prevalence of MetS in this cohort is almost double that of the general population, while the rate in Indigenous patients is among the highest reported for those with mental illness. Rehabilitation staff are encouraged to engage more fully in the monitoring of physical health status, sharing this information with consumers and primary care providers, and encouraging consumers to play a greater role in managing their physical health.